The Ontological Dimension of Adat Badamai in Legal Conflict Resolution: A Restorative Justice Perspective - Ahmad Mubarak; Nisa Adelia (Indonesian Journal Publisher, 2025)
This study aims to dissect the ontological dimension of Adat Badamai in legal conflict resolution through the lens of restorative justice. The primary focus is to understand the essential nature of local values as a foundation for living law within the community. This is normative legal research employing conceptual and legal philosophy approaches. The analysis is conducted on secondary legal materials, including customary law literature and theories of justice. Data are analyzed qualitatively and descriptively to dissect the norms and values embedded within Adat Badamai. The findings indicate that ontologically, Adat Badamai is rooted in the values of balance and communality, representing the existential nature of law as a living state of social equilibrium rather than mere dogmatic rules. From a restorative justice perspective, this norm perceives legal violations not merely as breaches of statutory law, but as a disruption of human relations. Adat Badamai serves as a normative bridge that prioritizes victim restitution and social reconciliation through a consensus that is both morally and legally binding. Philosophically, Adat Badamai holds a position as an independent legal norm relevant to the Pancasila legal ideals. Strengthening this ontological dimension provides theoretical legitimacy for the implementation of restorative justice that is deeply rooted in Indonesia's national identity.